DISPUTE RESOLUTION OF DUPLICATE OWNERSHIP RIGHTS CERTIFICATES (A STUDY AT THE SOUTH TAPANULI LAND OFFICE) - Abdul Malik; Taufik Siregar; Isnaini (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the causes of the issuance of duplicate Certificates of Ownership and the dispute resolution mechanism implemented by the South Tapanuli Land Office. The research employs an empirical juridical approach by combining library research with field research through document analysis and interviews with relevant parties. The collected data were analyzed qualitatively by comparing the applicable legal provisions with the facts found in land administration practices. The findings reveal that the issuance of duplicate certificates was primarily caused by weaknesses in administrative verification, an unclear history of land ownership, the absence of complete physical land records, and the limited integration of historical land registration data into the digital land administration system. The dispute was initially addressed through administrative examination and mediation facilitated by the Land Office to seek an amicable settlement. When mediation failed to produce an agreement, the parties retained the right to pursue litigation before the competent court. The study concludes that the effectiveness of preventing duplicate certificates depends on accurate land registration procedures, comprehensive verification of legal and physical data, and the integration of historical land records into a reliable digital administration system. In accordance with the principle of legal certainty in land registration, the certificate issued first generally possesses stronger legal standing, provided that it was issued in compliance with applicable legal requirements and is free from administrative defects.